Structural, Optical and Antibacterial Activity Studies on CMC/PVA Blend Filled with Three Different Types of Green Synthesized ZnO Nanoparticles - Yassin, A. Y.; Abdelghany, A. M.; Salama, Reda S.; Tarabiah, A. E. (Journal of inorganic and organometallic polymers and materials, 2023)
In this work, zinc oxide (ZnO) was produced using extracts of Thymus (Z), Hibiscus rosa-sinensis (K), and Daucus carota (G). Furthermore, sodium carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA) were combined with ZnO to form three novel nanocomposites. X-ray diffraction (XRD) was used for the structural analysis, where the semicrystalline nature of the (CMC/PVA)/ZnO nanocomposites was confirmed. The characteristics functional groups that arose inside the prepared samples were identified by Fourier transform infrared spectroscopy (FTIR). Evidence for the successful preparation of the pure ZnO particles and their nanocomposites was carried out using a transmission electron microscope (TEM). The ZnO nanoparticles are mostly spherical, irregularly distributed, and have radii ranging from 10 to 40 nm. Their anti-bacterial activity was studied against B. subtilis , E. coli, and Candida albicans . The inhibition zones of all the prepared samples against E. coli were 0, 19, 31, and 23 mm for PVA/CMC blend, PVA/CMC/ZnO (Z) (PCZ-Z), PVA/CMC/ZnO (K) (PCZ-K), and PVA/CMC/ZnO (G) (PCZ-G), respectively, compared to the streptomycin control Gram-positive standard with inhibition zone (34 mm). On the other hand, the inhibition zones of the prepared samples against B. subtilis were equal to 0, 26, 33, and 28 mm for CMC/PVA, PCZ-Z, PCZ-K, and PCZ-G, respectively. Based on these results, the PCZ-K sample is the most effective at resisting E. coli (91.17%) and B. subtilis (94.28%). These nanocomposites do not have harmful chemicals, making them strong candidates for use in biological applications.